Superior sporting performance in athletics: Determinants and sustainability - Meier, H. E.; Jetzke, M.; Nagm, A.; von Uechtritz, C. (Social Science Quarterly, 2019)
The article aims to contribute to the understanding of competitive dynamics and specialization in international sport by analyzing superior sporting performance (SSP) in international athletics in the period from 1999 to 2018. By applying iterative Kolmogorov-Smirnov tests to annual bests, the study examines national SSPs. Contrary to theoretical considerations, less specialized countries are more likely to achieve SSP. Technical entry barriers and macrosocial factors also appear to play a limited role. SSP seems not to disappear due to increased international competition. The United States and Russia are identified as "sporting super powers," able to persistently dominate a number of disciplines. The case of Russia poses fundamental questions concerning market distortions in international sport resulting from doping. The results come with substantial policy implications.